The role of coffee and potential mediators in subclinical atherosclerosis: insights from Mendelian randomization study - Yang, Qiwen; Yuan, Yue; Lyu, Diyang; Zhuang, Rui; Xue, Donghua; Niu, Chaofeng; Ma, Liyong; Zhang, Lijing (Frontiers in Nutrition, 2024)
Background and aims : Coffee contains many bioactive compounds, and its inconsistent association with subclinical atherosclerosis has been reported in observational studies. In this Mendelian randomization study, we investigated whether genetically predicted coffee consumption is associated with subclinical atherosclerosis, as well as the role of potential mediators. Methods : We first conducted a two-sample Mendelian randomization analysis to examine the causal effect of coffee and its subtypes on subclinical atherosclerosis inferred from coronary artery calcification (CAC). Next, the significant results were validated using another independent dataset. Two-step Mendelian randomization analyses were utilized to evaluate the causal pathway from coffee to subclinical atherosclerosis through potential mediators, including blood pressure, blood lipids, body mass index, and glycated hemoglobin. Mendelian randomization analyses were performed using the multiplicative random effects inverse-variance weighted method as the main approach, followed by a series of complementary methods and sensitivity analyses. Results : Coffee, filtered coffee, and instant coffee were associated with the risk of CAC (β = 0.79, 95% CI: 0.12 to 1.47, P = 0.022; β = 0.66, 95% CI: 0.17 to 1.15, P = 0.008; β = 0.66, 95% CI: 0.20 to 1.13, P = 0.005; respectively). While no significant causal relationship was found between decaffeinated coffee and CAC (β = -1.32, 95% CI: -2.67 to 0.04, P = 0.056). The association between coffee and CAC was validated in the replication analysis (β = 0.27, 95% CI: 0.07 to 0.48, P = 0.009). Body mass index mediated 39.98% of the effect of coffee on CAC (95% CI: 9.78% to 70.19%, P = 0.009), and 5.79% of the effect of instant coffee on CAC (95% CI: 0.54% to 11.04%, P = 0.030). Conclusion : Our study suggests that coffee other than decaffeinated coffee increases the risk of subclinical atherosclerosis inferred from CAC. Body mass index mediated 39.98% and 5.79% of the causal effects of coffee and instant coffee on CAC, respectively. Coffee should be consumed with caution, especially in individuals with established cardiovascular risk factors, and decaffeinated coffee appears to be a safer choice.